Small-strain shear modulus and shear strength of an unsaturated clayey sand - Georgetti, G. B.; Vilar, O. M.; Rodrigues, R. A. [UNESP] (My University, 2013)
This paper presents and discuss results of laboratory tests with a compacted clayey sand. Two sets of tests were performed to analyze the shear strength and the small-strain shear modulus (Go) of this soil. The first set consisted of triaxial compression tests performed on saturated specimens and multistage triaxial compression tests with controlled suction on unsaturated specimens, which were sheared under constant water content. The second set consisted of tests to measure the Go of specimens under constant suction using the bender elements technique. The results allowed observing the development of suction during shearing and influence of suction and confining stress on the shear strength and on the small-strain shear modulus of the tested soil. A planar failure envelope could nicely fit experimental data of shear strength. The influence of net confining stress on the small-strain shear modulus reduced as the suction increases. The shear modulus tended to increase non-linearly with suction, seeming to reach an asymptotic value.
Keywords: Bender elements; Shear modulus; Shear strength; Unsaturated soil